ANALISIS TRANSAKSI JUAL BELI ONLINE DI MARKETPLACE SHOPEE MENURUT KONSEP BISNIS ISLAM PADA MASA PANDEMI COVID 19 - Arhadian Roliansyah; Amelia Putri Utami; Asnaini, Asnaini; Nonie Afrianty (Juremi: Jurnal Riset Ekonomi, 2022)
This study aims to determine the comparison of online buying and selling transactions before and during the covid 19 pandemic, the positive and negative impacts of online buying and selling transactions on the shopee marketplace according to Islamic business ethics. This research method is library research using a qualitative approach. The results of this study indicate that there is an increase in transactions at Shopee, seen in the second quarter of 2020 reaching 260 million transactions. This number is up 130% compared to the second quarter of 2019. The positive impact of online buying and selling transactions is that it provides security and convenience in the transaction process, saves on promotional costs and increases transaction speed. The negative impact of online buying and selling transactions is that goods do not match the specifications of the goods that have been displayed on the sales display on the shopee marketplace. However, online buying and selling transactions on the shopee marketplace according to the Islamic business concept are allowed as long as the buying and selling transactions have implemented the principles of Islamic business ethics of unity, balance, free will, responsibility, truth; virtue and honesty so as not to cause harm in transactions.